The Odyssey - Lovell, Dyson 1940-; Konchalovsky, Andrei 1937- (Floor East Tower, Philippines VIVA Video, 2003)
Homer's engaging and edifying tale recounts the journey of Odysseus, king of Ithaca and mastermind of the Greek victory in Trojan war, who survives ten years of trials gods and makes his way home at last to his kingdom, his loyal wife and son with something more valuable than the spoils of war--wisdom.
Music composed and conducted by Edward Artemyev ; Editor, Michael Ellis ; Production designed by Roger Hall ; Director of photography, Sergei Koslov ; Executive producers, Robert Halmi, Sr., Francis Ford Coppola, Fred Fuchs.
Armand Assante, Greta Scacchi, Geraldine Chaplin, Jeroen Krabbe, Christopher Lee, Irene Papas.
DVD.
In English.
Keywords: War; Ancient Greek; Fiction